Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan di Kopigo Padang - Maulidia Putri; Yuke Permata Lisna (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research is encouraged by issues with service quality, cost, and consumer happiness. This kind of quantitative study employs the survey method and the causal associative approach (cause and effect). Primary and secondary data kinds are employed. This study examines Kopigo Padang customers. One hundred clients made up the research sample, which was selected using the non-probability sampling method. The data collection method was through a questionnaire, also known as a This makes use of a Likert scale whose validity and reliability have been examined. SPSS 26.00 was used to process the study data. Based on the results, the Service Quality Variable with a percentage of 55%, the Price Variable with a percentage of 70%, and the Customer Satisfaction Variable with a percentage of 62% were all in the right group. Regarding the service quality value (X1), the beta or standard coefficient is obtained, which is 0.479, with a T count of 7,167, and 0.000 <0.05 as the significant level. Customer satisfaction (Y) is positively impacted by the service quality variable (X1). A standardized coefficient of 0.493 Using a significance The 0.000 <0.05 threshold is found Regarding the price value (X2). Customer satisfaction (Y) is positively impacted by the pricing variable (X2). Additionally, we discovered an Adjusted R Square value of 0,877, indicating that There is an 87.7% influence of the independent variable on the dependent variable. 12.3% was contributed by additional variables that this study did not look into.